New research on the Urnfield period of Eastern Slovenia. A case study of Rogoza near Maribor - Črešnar, Matija (Arheološki vestnik, 2010)
The construction of the motorway network in Slove-nia uncovered an archaeological site at Rogoza, which became a case study for an Urnfield period settlement even before it was fully published. Potter y and radio-carbon dates, to some extent, indicate that the area was inhabited in other periods as well. It yielded finds from the Early Bronze Age, the Early Iron Age, the Late Iron Age and the Roman period.This paper introduces pottery, metal and stone finds from the Urnfield period and includes results of analyses of metal, stone finds, bones and plant remains. It also presents the development of the settlement at Rogoza and the Urnfield period settlement patterns in eastern Slovenia, knowledge of which has considerably increased during the last decade, marked by intense archaeological fieldwork.